Photoluminescence and Raman spectroscopy of Cd(S, Se) under hydrostatic pressure. Issue 4 (5th April 2013) - Sander, Thomas; Rinn, Markus S.; Klar, Peter J.
Abstract: A series of Cd(S, Se) crystals grown by a sublimation method ranging from pure CdS to CdSe were investigated by photoluminescence (PL) and Raman spectroscopy under hydrostatic pressure. The ternary alloy Cd(S, Se) crystallizes in a direct bandgap wurtzite structure at ambient pressure. It undergoes a phase transition to an indirect bandgap rocksalt structure between a pressure of 2 and 3.5 GPa. According to group theory the wurtzite structure possesses four Raman modes whereas the rocksalt structure does not exhibit any active first order Raman modes. Upon release of pressure the Raman signals are recovered whereas the PL signals do not reappear. This may indicate that small domains with rocksalt structure still exist after cycling through the phase transition and thus lead to a nonradiative recombination. The pressure dependence of the longitudinal optical phonons of the ternary alloy were estimated. The pressure slopes tend to increase with the selenium concentration in the samples. This effect can be explained by changing of the bulk modulus from small for CdSe to large for CdS. Furthermore, Grüneisen parameters have been calculated for Cd(S, Se), assuming a linear relationship between the bulk moduli of the pure materials CdS and CdSe.